Economic Uncertainty And The Demand For Money In Thailand - Chong, Mei Teing (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study empirically examines the economic uncertainty and the demand for money in Thailand by utilising quarterly data covering the period of l 980Q 1 to 20 l 3Q4. Within· the sample period, Thailand had gone through some critical times such as financial liberalisation, Asian financial crisis, tsunami, flood, and so on. These events indirectly inspiring the motive to unravel the demand for money in the past couple ten years when the variability of the economy was staggered. Several econometric techniques are employed in particular to test on the sample, include general autoregressive conditional heteroscedasticity model, unit root tests, cointegration test, and Granger causality test. Empirical results show that economic uncertainty index has well captured the heightened periods of economic uncertainty from the six constituents. Economic uncertainty is found to have stable long run relationship with Ml and M2. Despite using inflation targeting regime to maintain price stability, monetary targeting serves as an alternative way where the monetary aggregate Ml and M2 are deemed appropriate to be targeted.